2002
DOI: 10.1159/000071572
|View full text |Cite
|
Sign up to set email alerts
|

Escape from X inactivation

Abstract: Although the process of X inactivation in mammalian cells silences the majority of genes on the inactivated X chromosome, some genes escape this chromosome-wide silencing. Genes that escape X inactivation present a unique opportunity to study the process of silencing and the mechanisms that protect some genes from being turned off. In this review, we will discuss evolutionary aspects of escape from X inactivation, in relation to the divergence of the sex chromosomes. Molecular characteristics, expression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 75 publications
4
87
0
3
Order By: Relevance
“…3) 61,68 . In mouse, we found that the LINE/L1 density is elevated in both the XCR (35%) and the XAR (32%), which is consistent with the observation that genes that escape inactivation on the human XAR are often inactivated in mouse 69 . As previously observed in human 68 , the LINE/L1 elevation in mouse is particularly dramatic among recent, lineage-specific subfamilies ( Supplementary Fig.…”
Section: Chromosome Inactivationsupporting
confidence: 89%
“…3) 61,68 . In mouse, we found that the LINE/L1 density is elevated in both the XCR (35%) and the XAR (32%), which is consistent with the observation that genes that escape inactivation on the human XAR are often inactivated in mouse 69 . As previously observed in human 68 , the LINE/L1 elevation in mouse is particularly dramatic among recent, lineage-specific subfamilies ( Supplementary Fig.…”
Section: Chromosome Inactivationsupporting
confidence: 89%
“…The analysis yielded three biologically informative sets. One consists of genes escaping X inactivation [merged from two sources (13,14) that largely overlap], discovering the expected enrichment in female cells. Two additional sets consist of genes enriched in reproductive tissues (testis and uterus), which is notable inasmuch as mRNA expression was measured in lymphoblastoid cells.…”
Section: Resultsmentioning
confidence: 99%
“…These reactions include loss and restructuring of low-copy DNA sequences (Song et al, 1995;Feldman et al, 1997;Ozkan et al, 2001Ozkan et al, , 2002Shaked et al, 2001;Kashkush et al, 2002), activation of genes and retrotransposons (O'Neill et al, 2002;Kashkush et al, 2003), gene silencing (Chen and Pikaard, 1997a, b;Comai et al, 2000;Lee and Chen, 2001), and subfunctionalization of gene expression patterns (Adams et al, 2003(Adams et al, , 2004Samuel Yang et al, 2006;Hovav et al, 2008). These responses are closely paralleled in animals by inactivation (Lee and Jaenisch, 1997;Avner and Heard, 2001) and differential regulation of X-chromosome gene expression (Disteche et al, 2002;Parisi et al, 2003) and retroelement activation (O'Neill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%